Answer:
a) Find the common ratio of this sequence.
Answer: -0.82
b) Find the sum to infinity of this sequence.
Answer: 2.2
Step-by-step explanation:
nth term in geometric series is given by ![4\ th \ term = ar^n-1\\-2.196 = 4r^{4-1} \\-2.196/4 = r^{3} \\r = \sqrt[3]{0.549} \\r = 0.82](https://tex.z-dn.net/?f=4%5C%20th%20%5C%20term%20%3D%20ar%5En-1%5C%5C-2.196%20%3D%204r%5E%7B4-1%7D%20%5C%5C-2.196%2F4%20%3D%20r%5E%7B3%7D%20%5C%5Cr%20%3D%20%5Csqrt%5B3%5D%7B0.549%7D%20%5C%5Cr%20%3D%200.82)
where
a is the first term
r is the common ratio and
n is the nth term
_________________________________
given
a = 4
4th term = -2.196
let
common ratio of this sequence. be r
![4\ th \ term = ar^n-1\\-2.196 = 4r^{4-1} \\-2.196/4 = r^{3} \\r = \sqrt[3]{-0.549} \\r = -0.82](https://tex.z-dn.net/?f=4%5C%20th%20%5C%20term%20%3D%20ar%5En-1%5C%5C-2.196%20%3D%204r%5E%7B4-1%7D%20%5C%5C-2.196%2F4%20%3D%20r%5E%7B3%7D%20%5C%5Cr%20%3D%20%5Csqrt%5B3%5D%7B-0.549%7D%20%5C%5Cr%20%3D%20-0.82)
a) Find the common ratio of this sequence.
answer: -0.82
sum of infinity of geometric sequence is given by = a/(1-r)
thus,
sum to infinity of this sequence = 4/(1-(-0.82) = 4/1.82 = 2.2
If n = the term number, then:
A(4) = 6-4(4-1)
A(4) = 6-4(3)
A(4) = 6-12
A(4) = -6
A = -1.5
5.
f(K) = D^3 => f(25) = 125 => 25 * t = 125 ( because K is directly proportional with D^3 )=> t = 125 / 25 => t = 5 => f(25) = 25 * 5 => K * 5 = D^3 ;
6.
f(L) = F^3 => f(2) =3^3 =>f(2) = 27 => 2 / t =27 => t = 2 / 27 => t = 0.074 => f(2) = 2 / 0.074 => K / 0.074 = F^3 ;
-3 from all ends to get 1<-3x<3 then divide by -3 on all ends to get -1/3>x>-1 you flip the sign because of the negative,
Answer:
20/49
Step-by-step explanation: